Rademikibart (CBP‐201), a next‐generation monoclonal antibody targeting human IL‐4Rα: Two phase I randomized trials, in healthy individuals and patients with atopic dermatitis - Junying Wang; Jeffery White; Kenneth J. Sansone; Lynda Spelman; Rodney Sinclair; Xin Yang; Wubin Pan; Zheng Wei (Wiley, 2023)
Abstract IL‐4 and IL‐13 signaling via IL‐4Rα plays key roles in the pathogenesis of atopic dermatitis (AD) and asthma. Rademikibart (formerly CBP‐201), a next‐generation human IgG4 kappa monoclonal antibody, blocks IL‐4Rα‐mediated signal transduction. We performed two phase I, randomized, double‐blind, placebo‐controlled trials. In a single‐ascending dose trial, 40 healthy adults were randomized 3:1 to rademikibart (75-600 mg s.c., 300 mg i.v.) or placebo, with 12 weeks of follow‐up. In the multiple‐ascending dose trial, 31 adults with moderate‐to‐severe AD were randomized 4:1 to once weekly rademikibart (75-300 mg s.c.) or placebo for 4 weeks, plus 7 weeks of follow‐up. Most treatment‐emergent adverse events (TEAEs) were mild; none were serious. Two s.c. injection site reactions and one TEAE of conjunctivitis were reported, all were mild. Rapid and sustained improvements were observed in AD severity and in quality of life (QoL), without plateauing. At week 4, efficacy scores improved by a maximum of −74.4% (Eczema Area and Severity Index), −62.7% (body surface area), −52.8% (Pruritus Numerical Rating Scale [PNRS] severity), −54.4% (PNRS frequency), and − 69.9% (Dermatology Life Quality Index). Thymus activation regulated chemokine inflammatory biomarker concentrations decreased in both trials (−55.4% in the pooled rademikibart arms vs. +18.0% with placebo, at week 5, in patients with AD). Exposure to rademikibart increased in a greater than dose‐proportional manner, suggesting nonlinear clearance. In summary, rademikibart was well‐tolerated and associated with rapid and sustained improvements in eczematous lesions, pruritus, QoL, and inflammatory biomarker concentrations during 4 weeks of treatment. Efficacy responses did not plateau and were generally dose dependent. These promising findings support further development of rademikibart in patients with AD.